A Novel CD3G Mutation in a Taiwanese Patient With Normal T Regulatory Function Presenting With the CVID Phenotype Free of Autoimmunity—Analysis of all Genotypes and Phenotypes - Lee, Wen-I; Fan, Wen-Lang; Lu, Chun-Hao; Chen, Shih-Hsiang; Kuo, Ming-Ling; Lin, Syh-Jae; Tsai, Weng-Sheng; Jaing, Tang-Her; Chen, Li-Chen; Yeh, Kuo-Wei; Yao, Tsung-Chieh; Huang, Jing-Long (Frontiers in Immunology, 2019)
The T-cell receptor (TCR)/CD3 complex is crucial for T cell development and regulation. In humans, CD3D, CD3E and CD3Z gene defects cause severe combined T and B cell immunodeficiency. However, CD3G mutations alone lead to a less severe condition, which is mainly characterized by autoimmunity. In the present study, we report the case of a 36-year-old male who presented with recurrent sinopulmonary infections without opportunistic infections; this was compatible with hypogammaglobulinemia but he had normal PHA-lymphocyte proliferation. This patient had the common variable immunodeficiency (CVID) phenotype, and received regular immunoglobulin infusions over 20 years; he gradually developed nodular regenerative hyperplasia over a 5-year period. Distinct from the previously reported CD3G mutations, which mainly present as autoimmunity, the novel CD3G deletion (c.del213A) in our patient caused an obvious decrease in switched memory B cells and diminished CD40L expression. However, sufficient Treg suppression function was maintained so that he remained free of autoimmune thyroiditis (AIT), inflammatory bowel disease (IBD) and autoimmune pancytopenia. A PubMed search of this rare disease entity revealed seven Turkish and two Spanish patients (five unrelated families). Among a total of 20 alleles, there were 14 splicing mutations (80(-1)G>C), two missense mutations (c.1G>A), two nonsense mutations (c.250A>T), and two deletions (c.del213A). Three patients presented with isolated AIT without significant infections. Three patients died, one from a severe infection at 31 months, one from post-transplant respiratory failure due to viral pneumonia at 17 months, and one from graft versus host disease at 47 months. Those experiencing opportunistic infections, severe life-threatening infections in need of hematopoietic stem cell transplantation, and IBD-like diarrhea had a significantly higher mortality rate compared with those without these features (p=0.0124, p=0.01 and p=0.0124, respectively). The patients with AIT had a significantly better prognosis (p=0.0124) compared with those without AIT. Our patient with the novel CD3G mutation presented with predominant B cell deficiency overlapping with the CVID phenotype but without recognizable autoimmunity, which was consistent with his normal Treg suppression function.